Prediksi Profitabilitas, Likuiditas, Leverage, Sales Growth, dan Managerial Agency Cost terhadap Financial Distress pada Perusahaan Sektor Transporation and Logistic yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Angwen Cahyani, Anggur; Hartono, Ulil (Universitas Negeri Surabaya, 2024)
The current world financial crisis has caused many bankruptcies in various companies. So, it is necessary to anticipate the occurrence of financial distress so that businesses can prevent this action. This study analyses the prediction of profitability, liquidity, leverage, sales growth, and managerial agency costs in financial distress. The population in this study was 27 companies in the transportation and logistics sector listed on the IDX and published financial reports annually during 2019–2022. The sample used was 14 companies, with sampling techniques through purposive sampling. The data analysis in this test utilizes logistic regression analysis. The results of this test show that profitability, liquidity, leverage, sales growth, and managerial agency cost can predict financial distress, but the results of the effect test in this study state that all independent variables consisting of profitability, liquidity, leverage, sales growth, and managerial agency cost do not affect financial distress. Therefore, researchers recommend utilizing this test model to predict financial distress because the accuracy that can be given is quite good so that companies can anticipate financial difficulties.